Erythema Induratum of Bazin – A Rare Entity - Yasmin, Rifat; Haq, Anwar ul (International Journal of Pathology, 2018)
Erythema Induratum of Bazin (EIB) is a tuberculid, a condition occurring ‘on the legs of femaleand in young and plump well nourished women. It is characterized by recurrent nodular andulcerative lesions. Lesions are usually localized to the lower legs especially calf area, but can affectother areas. We are presenting a case of a 54-years-old lady with recurrent crops of nodules onlegs. Mantoux test was positive. Histopathology revealed lobular panniculitis, epithelioid cells,lymphocytes and giant cells surrounding foci of caseous necrosis which was suggestive of erythemainduratum. She was put on ATT.Keywords: Erythema induratum, Nodular vasculitis, Cutaneous tuberculosis, Tuberculid,Tuberculous granuloma, Panniculitis